2016
DOI: 10.1104/pp.16.00821
|View full text |Cite
|
Sign up to set email alerts
|

A Collection of Conserved Noncoding Sequences to Study Gene Regulation in Flowering Plants

Abstract: Transcription factors (TFs) regulate gene expression by binding cis-regulatory elements, of which the identification remains an ongoing challenge owing to the prevalence of large numbers of nonfunctional TF binding sites. Powerful comparative genomics methods, such as phylogenetic footprinting, can be used for the detection of conserved noncoding sequences (CNSs), which are functionally constrained and can greatly help in reducing the number of false-positive elements. In this study, we applied a phylogenetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 83 publications
4
21
0
Order By: Relevance
“…random occurrence of the shortest CNS (15bp). TFBS colocalize with accessible chromatin in mammalian genomes, as do CNS as demonstrated previously in plants (4,(9)(10)(11)(12)(13)(14) .…”
supporting
confidence: 78%
“…random occurrence of the shortest CNS (15bp). TFBS colocalize with accessible chromatin in mammalian genomes, as do CNS as demonstrated previously in plants (4,(9)(10)(11)(12)(13)(14) .…”
supporting
confidence: 78%
“…The InterPro PP2C domain “IPR001932” was used to search the Plaza3.0 database ( http://bioinformatics.psb.ugent.be/plaza/ ) in order to identify PP2C candidate genes in M . truncatula 50 . Amino acid sequences (Supplementary Data 1 ), CDS sequences (Supplementary Data 2 ) and Genomic sequences (Supplementary Data 3 ) of PP2C genes in M .…”
Section: Methodsmentioning
confidence: 99%
“…In animals, many CNSs are large (R100 bp) (Stephen et al, 2008), while different analyses in plants have primarily identified smaller (15-50 bp) CNSs (Thomas et al, 2007;Baxter et al, 2012;Haudry et al, 2013;Turco et al, 2013). Various algorithmic approaches are currently employed to identify CNSs in plants including both manual (Thomas et al, 2007) and automated (Turco et al, 2013) curation of BLASTN results, global alignments of sliding windows of promoter regions (Baxter et al, 2012), the use of whole-genome alignment algorithms (Haudry et al, 2013), alignment-independent detection of enriched IUPAC motifs (De Witte et al, 2015), and searches for biologically defined transcription factor binding sites across orthologous genes (Van de Velde et al, 2016). The majority of these approaches are either based on two-at-a-time sequence alignments (Baxter et al, 2012;Haudry et al, 2013;Turco et al, 2013) and/or do not retain information on conserved microsynteny within the promoter (De Witte et al, 2015;Van de Velde et al, 2016).…”
Section: Introductionmentioning
confidence: 99%